The influence of principal leadership and organizational climate on teacher performance - Akbariah Rahmah; Muhammad Kristiawan; Destiniar Destiniar (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study examined the level of the principal's influence leadership and organizational climate on both partial and simultaneous on teacher’s performance. This study was quantitative methods. Data were analyzed using multiple linear regression formula using SPSS version 22.0 for windows. The results of this study indicate that there is a significant effect of principal leadership and organizational climate together on teacher performance with an f-count value of 114,997 f-table of 3.13. The conclusion of this study is that to improve teacher performance, principal leadership and a good organizational climate are needed.